ENGLISH LANGUAGE INTSTRUCTION IN CULTURAL MANAGEMENT - Tihomir Živić (European Scientific Journal, ESJ, 2015)
Cultural Management is one of the three courses of universitarian interdisciplinary undergraduate and graduate Cultural Studies, the first of a kind at the Josip Juraj Strossmayer University in Osijek. The course is based on a common original module of Cultural Studies, providing for a foundation of general theoretical knowledge intrinsic to the interdisciplinary studies, whereby Cultural Studies are a multidisciplinary area with a versatile research objective and methodological framework, encompassing a wide spectrum of analytical fields dealing with culture. Such a common program is performed within undergraduate and graduate studies, while the Cultural Management course facilitates an acquisition of specialized knowledge, necessary skills, and narrower competencies for an efficacious cultural management. Differentiating education (i.e., an institutionalized form of learning, usually related to a juvenile age) and learning, the English Language instruction within the Cultural Management course endeavors to suppress an inconvenience of “return to the school benches” while promoting a habit of students’ lifelong learning (i.e., of a spontaneous, informal knowledge acquisition irrespective of their age), in conformity with the Croatian Adult Education Strategy. In addition to interdisciplinarity, such an open study model aims to promote an acquisition of theoretical knowledge in various English analytical discourses (e.g., , information science theory, theory of nation, educational theory, cultural anthropology, cultural studies, deconstruction, New Historicism, gender studies, environmental studies, postcolonial studies, subcultural theories, etc.) as well, perplexing it with a professional practice directly.